Evaluation of Product Quality Improvement Against Waste in the Electronic Musical Instrument Industry - Hendra Hendra; Indra Setiawan; Hernadewita Hernadewita; Hermiyetti Hermiyetti (Universitas Ahmad Dahlan, 2021)
Customer satisfaction is one of the main factors that must be considered by every company to compete in the global market. One way to increase customer satisfaction is to reduce defective products and reduce waste. This method is a continuous improvement that must be carried out by every manufacturing industry. The Musical Instrument Industry is one of the producers of electronic musical instruments such as pianos. The production process has occurred several problems such as low product quality and waste (ineffective processes, inappropriate layouts, overproduction, and poor production quality). The biggest problem with this company is the large number of products that are not following company standards, such as not achieving quality standards and production not achieving targets. To improve the quality of its production, companies need to make the production process streamlined so that it will create a more effective and efficient production line. A balance between effectiveness and efficiency can be made by reducing waste. Lean Six Sigma is an approach that focuses on improving quality and eliminating waste and sustainable strategy to improve product quality while reducing waste. The company's strategy to be able to compete in the global market must be able to improve product quality and eliminate waste. This study aims to improve product quality and analyze the effect of improving quality on waste. The method used is Lean Six Sigma with dynamo stages, namely pre-study, measurement, analysis, and implementation. The results showed that the quality of the product had increased. Quality improvement has a significant effect on waste.